СКРЫТЫЙ ГЕПАТИТ В: КЛИНИЧЕСКОЕ ЗНАЧЕНИЕ И ПРОБЛЕМЫ ДИАГНОСТИКИ - И. А. Морозов; Л. Ю. Ильченко; И. Г. Федоров; И. В. Гордейчук; И. Н. Гордейчук; А. К. Княженцева; Е. А. Зверкова; М. И. Михайлов; Г. И. Сторожаков (Архивъ внутренней медицины, 2012)
In this report we present current data on prevalence, clinical significance and methods of diagnostics of occult hepatitis B. Mechanisms of occult hepatitis B formation are reviewed, among which the most important is co-infection with other hepatotropic viruses. Diagnostic significance of anti-HBcAg antibodies is shown. An algorithm of occult hepatitis B detection developed by the authors involves two stages: detection of viral markers in serum and liver tissue. Attention is drawn to the role of morphologic methods including histochemistry, immunohistochemistry and electron microscopy in verification of HBVinfection and direct visualization of virions in cytoplasm of hepatocytes.